Development Textbooks E-Commerce for Growing Entrepreneurship Skills - Sigitta, Rito Cipta; Prasetyono, Rizki Noor (Institut Teknologi Dirgantara Adisutjipto, 2019)
In the digital and disrupt era 4.0 requires innovation in meeting human needs, especially in commerce. The purpose of this study is to increase student interest in entrepreneurship through e-commerce textbooks. This research is a research and development research with ADDIE model. Product validity data collection using questionnaires and tests to find out the increase in entrepreneurship. The results of data analysis and discussion can be concluded that from the development of e-commerce teaching materials validation of material experts, media experts and peers shows that products in the excellent category are appropriate to use. Small group product trials obtained an ideal percentage of 85.2% and were categorized very well. The results of the analysis of increasing entrepreneurial skills from the use of e-commerce teaching materials obtained an N-Gain value of 0.45, indicating that e-commerce development to improve entrepreneurship capacity is effective and appropriate for use in the learning process.